Torta de mamona destoxificada por soluções alcalinas em dietas de fêmeas caprinas leiteiras - Araújo, Ricardo Alves de (2019)
The objective of this work was to develop an efficient and viable detoxification of castor bean cake, and to evaluate its effect as a potential replacement of soybean meal on the productive performance and cost of dairy goats at different stages of production. The experiment was conducted at Embrapa Goats and Sheep, Sobral-CE, from January 2015 to May 2017. In the first chapter were tested two alkaline products, they are: calcium hydroxide [Ca(OH)2] and sodium hydroxide (NaOH), diluted in different volumes of water, thus forming different concentrations of solutions on the inactivation of ricin and ricinus agglutinates, chemical composition, in situ degradability and fractionation of proteins of the detoxified castor. The proportions were tested: 60 and 90 g of both products diluted in 1,000; 1,500; 2,000 and 2,500 ml of water for each kilo of castor bean cake. The analyzes were performed detoxification through visual observation and by bone densitometry of electrophoresis gels, and hemagglutination assays. It was observed that the different concentrations used, only the use of 90 and 60 grams of Ca(OH)2 and NaOH, respectively managed to destoxificar 100% of the DCC, both diluted in 2,000 ml of water. On the other hand, when assessing the minimum time of contact of the reagents with the DCC for maximum detoxification, it was observed that with three hours of contact is the time required for the reagents decrease in 100% of the cytotoxic proteins, in addition to not leave hemagglutinating activity in this material. To evaluate the degradability of DM of detoxified castor cake (DCC), we observed that the DCC Ca(OH)2 increased by 10.06% of the fraction α, already the DCC NaOH 22.53%. In a general way, the parameters of degradation were higher for the DCC NaOH. Similarly, it was noted that the detoxification with NaOH provided greater degradation of soluble proteins and degradation increased, favoring the provision of non-protein nitrogen. The alkali treatments with Ca(OH)2 or NaOH at doses of 90 and 60 grams per kilo of DCC, respectively and diluted in 2,000 ml of water per 180 minutes of contact may allow the use of the DCC in ruminant feed, but its application in industrial scale depends on operational feasibility studies and cost. In the second chapter of this study was to evaluate the influence of the substitution of soybean meal (SM) by detoxified castor cake (DCC) by two alkaline products on intake, performance, digestibility of nutrients, nitrogen balance and hepatic and renal function of goats’ kids during the growth phase. Were used twenty-four goats’ kids of Saanen breeds and Anglo Nubian, with initial body weight of 16.22 ± 0.67 kg. The treatments consisted of three diets: one to the base of DCC and the other two on the basis of detoxified castor with calcium hydroxide [Ca(OH)2) or sodium hydroxide (NaOH). It was used a completely randomized design with a factorial arrangement 3 x 2 (diet and breed). The experimental period lasted 270 days. The data of consumption and digestibility were analyzed in two distinct phases, according to the growth curves of goats’ kids, being a linear accelerated growth phase (Phase I, 60 to 298 days of life) and the other to reduce the intensity of body growth (Phase II, 299 to 345 days of life). There was no effect (P<0.05) of diets on the consumption of DM and nutrients in both phases. There was no effect (P> 0.05) of diets on the performance of the animals. The diets influenced (P <0.05) The coefficients of apparent digestibility of dry matter and nutrients, where the higher values corresponded to diets with DCC. No negative change involving renal or hepatic dysfunction was observed. The inclusion of castor cake in the diet of goats’ kids recreated in confinement is an attractive option, whereas the goats fed with DCC present better feed conversion and its use does not cause changes in liver and kidney, suggesting that the SM can be completely replaced. In the third chapter of this study was to evaluate the influence of the substitution of soybean meal (SM) by detoxified castor (DCC) by two alkaline products on the feeding behavior and physiological parameters of goat’s kids of Saanen breeds and Anglo Nubian. It was used a completely randomized design with a factorial arrangement 3 x 2 (diet and breed). There was no effect of diets on the consumption of DM and NDFap, with lower values for the goats fed with NaOH DCC. The goats of NaOH DCC diet consumed larger quantities of water and the saanen urinate more times that the Anglo Nubian. In this chapter, it was concluded that, when used in the composition of diets for goats in the growth phase, the detoxified castor with sodium hydroxide leads to the reduction of intake DM, as well as the NDF. In the fourth chapter we evaluated the influence of the total substitution of soybean meal (SM) by detoxified castor (DCC) by two alkaline products on the economic and financial viability in the production of dairy breeds arrays of Saanen and Anglo Nubian. The economic and financial evaluation of the data was carried out in a descriptive way, using the AVETEC® software. In the scenarios assessed, power, labor costs and the opportunities were the items that most contributed to the costs of production. The simulation for production of 144 dairy arrays provided revenue above the cost of production, resulting in positive economic indicators for all scenarios evaluated. It was observed that all scenarios had leveling point less than 144 goats that is the number of animals that can be produced annually by each type of creation. The indices of profitability are very attractive, especially those systems that opt for the foal of Saanen goats, where the NPVs are higher there are a million reais. Sensitivity analyzes showed that only in the most unfavorable situations, such as a reduction of 30% in both production and market price, the indicators are economically unviable. The use of the DCC does not compromise the economic viability of the systems, but when compared to systems that uses the standard diet, show lower profitability. In the fifth chapter of this study was to evaluate the influence of the substitution of soybean meal (SM) by detoxified castor (DCC) on performance, digestibility of nutrients, nitrogen balance, hepatic and renal functions of pregnant goats fed with diets containing DCC by alkaline solutions in confinement regime during the stages of pregnancy (first two thirds third and final). The experimental conditions and methodology were similar to those reported in the second chapter, except the amount of animals, in this case 18 goats were used, being 9 of the Saanen goats and 9 Anglo Nubian, primipara, not breastfeeding, with approximate age of 12 months, initial body weight of 42.08 ± 5.33 kg of body condition score of 3.6 ± 0.3, distributed in a completely randomized design, in plots subdivided in time, getting in the gestational phase plots and subplots the diets. In general, the goats fed with NaOH DCC had lower consumption. In addition, we observed a significant reduction in the consumption during the final third of pregnancy. There was no effect (P>0.05) of diets or phases on the digestibility of DM and nutrients. The average levels of enzymes for hepatic and renal functions were within normal patterns. Of enzymes related to liver metabolism, only the gamma-glutamyl transferase increased in the final third of the pregnancy. It was observed that the weight of the goats generated was not influenced by the diets, nor the body condition score of goats in the postpartum period. During the final third of gestation, the goats reduce sharply the DM intake and nutrients. In the sixth chapter was evaluated food behavior and physiological parameters of pregnant goats and fed with diets containing DCC by alkaline solutions in confinement regime during the stages of pregnancy (first two thirds third and final). The experimental conditions and methodologies were similar to those reported in the third chapter, with the exception of animals, in this case 18 goats were used. The goats fed with NaOH DCC showed the lowest fuel consumption, both MS and NDFap (P<0.05). In general, the goats decreased consumption in the final third of pregnancy. The detoxified castor with sodium hydroxide reduces the dry matter intake and feed efficiency of goats during pregnancy. The physiological parameters are influenced both by the diets as the stages of pregnancy, but without negative changes indicating that animal stress or discomfort. In the seventh chapter aimed to evaluate the intake, digestibility and nitrogen balance, curves of lactation, milk composition and metabolic profile kidney and liver of lactating goats fed diets containing detoxified castor (DCC) by alkaline solutions in feedlot during 150 days of lactation. The experimental design was in randomized casualization (factor breed), the experimental conditions and methodologies were similar to those reported in the second chapter, with the exception of the quantity of animals, in this case 18 goats were used. It has been observed that during the phase of lactation diets influenced (P<0.05) intake of DM, CP, EE, NDF and TDN. We observed a higher intake DM for the goats fed with SM which did not differ from goats fed with Ca(OH)2 DCC. The goats fed with SM consumed a larger quantity of nitrogen, but all had the same nitrogen balance, which shows that the fed with the DCC were efficient. There was no effect (P<0.05) of diets on milk production, milk corrected for 3.5% fat, total production and feed efficiency. The goats fed with SM and Ca(OH)2 DCC produced a larger quantity of milk. In summary, the lactation curves showed greater persistence of lactation of Saanen goats. There was no effect (P<0.05) of diets on the profile of some fatty acids present in the milk. In general, it was observed that the NaOH DCC provided an increase in the fat content of desirable fatty acids. It was concluded that both pies decrease milk production during the lactational period, however, the NaOH DCC provided high productive efficiency. Although both cakes diminish the yield of milk, the NaOH DCC did not affect negatively the content of fatty acids desirable and beneficial to human health, unlike the Ca(OH)2 DCC. In the eighth chapter was evaluated the ingestive behavior and physiological parameters of lactating goats fed diets containing detoxified castor. The experimental conditions and methodology were similar to those reported in the third chapter, except the number of animals, in this case 18 goats were used, being 9 of the Saanen goats and 9 Anglo Nubian. We observed effect of diets on the consumption of DM and NDFap, with lower values for the goats fed with NaOH DCC. In the ninth chapter was analyzed the economic and financial viability of the use of the detoxified pie by alkaline solutions in the production of goats of dairy origin, in addition to the marketing of milk produced by goats fed with the cakes of castor bean and soybean meal. The economic analyzes were performed using the same methodology in the fourth chapter, but there was a simulation of a revolution of the flock, considering that the producer began to generate two revenue inside the property. Six were simulated systems. Both the supply and the labor costs and the opportunities were the items that most contributed to the costs of production. The higher costs with power were observed in systems that have used the diets based on SM. The simulation for milk production and calves from 72 dairy goats provided revenue above the cost of production, resulting in positive economic indicators for all scenarios evaluated. The revenue generated by the systems that utilize the Saanen goats are bigger, considering that the price of the product generated is more valued in the market goat. On the other hand, the Saanen goats fed with DCC, due to their lower costs with greater power generated net revenue. The economic-financial analysis of the diets evaluated proved to be viable over 10 years with the interest rate of 6% per year. In a general way, the systems of rearing goats Anglo nubian, although they have presented positive NPVs, showed lower values in relation to the systems of creation of Saanen goats, with the exception of that used the diet on the basis of NaOH DCC. In relation to the payback, all diets had low time of return on investment applied, with values of less than three years for the Saanen and between 3.19 to 4.03 for the Anglo nubian, with emphasis on the system that uses NaOH DCC.